The Strategy Process / Concepts, Contexts, Cases: Third Edition - Mintzberg Henry; Quin Brian James (Prentice Hall International, 1996)
Acknowledgements, Introduction, Strategy, The Strategy Concept, The Strategist, Formulating Strategy, Strategy Analysis, Strategy Formation, Dealing with Structure and Systems, Dealing with Culture and Power, Managerial Styles, The Entrepreneurial Context, The Mature Context, The Professional Context, The Innovation Context, The Diversified Context, The International Context, Managing Changes, Case Notes, Bibliography for Readings, Name and Subject Index.
Acknowledgements, Introduction, Strategy, The Strategy Concept, The Strategist, Formulating Strategy, Strategy Analysis, Strategy Formation, Dealing with Structure and Systems, Dealing with Culture and Power, Managerial Styles, The Entrepreneurial Context, The Mature Context, The Professional Context, The Innovation Context, The Diversified Context, The International Context, Managing Changes, Case Notes, Bibliography for Readings, Name and Subject Index.